ANALISIS KUALITAS AIR GUNA MENDUKUNG PENGEMBANGAN BUDIDAYA IKAN BERBASIS KERAMBA JARING APUNG (KJA) DI PERAIRAN PANTAI ELAK-ELAK SEKOTONG - Damai Diniariwisan; Muhammad Sumsanto (Jurnal Perikanan Pantura (JPP), 2024)
Elak-elak Beach are a coastal area that is used for tourism and fishing activities in the form of traditional fishing systems. The potential is quite good for cultivation activities, making this area considered quite suitable for developing KJA activities. The aim of this research is to analyze water quality to see the suitability of the area to support marine cage-based fish cultivation development activities. The method used is descriptive with a purposive sampling system, to describe current conditions. The results of water quality measurements show that the temperature range is 30-32 °C, pH 7.6-7.8 and salinity 30 ppt, where these figures indicate a normal range. For DO, the results show >5 mg/l, which means it is suitable for the needs of aquatic biota, especially cultivated biota. Meanwhile, the nutrient content measured through phosphate and nitrate levels also showed quite high results, namely 0.025 – 0.03 mg/l for phosphate and 0.01 – 0.05 mg/l for nitrate. This range of values ​​indicates eutrophic waters, so that overall the Elak-elak Beach water area is good enough for the development of marine cage-based cultivation.